Two cases of immunoglobulin G4 (IgG4)-related hypophysitis diagnosed without pituitary biopsy. (June 2020) - Ma, Wanlu; Wang, Xi; Nie, Min; Fu, Junling; Mao, Jiangfeng; Wu, Xueyan
Background: Immunoglobulin G4-related hypophysitis (IgG4-RH) is a rare disease, diagnosis of which typically depends on histopathology following an invasive pituitary biopsy, possibly leading to permanent hypopituitarism. Herein, we report two cases of IgG4-RH with favorable responses to glucocorticoids. One of them was multiple organs involved and treated with glucocorticoids and methotrexate. Methods: We retrospectively review clinical features, radiological images, and treatment of two cases with IgG4-RH. In addition, literature on IgG4-RH was comprehensively reviewed and a new therapeutic strategy for IgG4-RH was provided. Results: A 45-year-old man presented with diabetes insipidus for 6 months. Pituitary magnetic resonance imaging (MRI) indicated thickening of pituitary stalk. His serum IgG4 was 13, 500 mg/l and hormonal evaluation revealed isolated growth hormone deficiency. Pituitary biopsy was denied by the patient due to fears of permanent pituitary damage. Treatment with prednisone and methotrexate (MTX) for 1 week led to improvement in sellar images and reduction in IgG4 level. His IGF1 (insulin-like growth factor-1) recovered after a 4-month treatment. The second case is a 43-year-old woman presenting with diabetes insipidus and amenorrhea for 20 months. Her pituitary MRI was similar to the patient above. Her serum IgG4 level was 5980 mg/l and hormonal measurement confirmed isolated hypogonadotropic hypogonadism. After 2 weeks of prednisone, the sellar images improved. After 3 months of treatment, her pituitary MRI was normal, IgG4 level had decreased to near normal range, and menstruation resumed. Literature review found additional patients with IgG4-RH, who were treated successfully without invasive pituitary biopsy in a manner similar to our cases. Therefore, we discuss the necessity of invasive pituitary biopsy for IgG4-RH. Conclusion: For suspected IgG4-RH with pituitary hormone deficiency, biopsy-induced hypopituitarism may be avoided by using diagnostic glucocorticoid treatment. Impaired pituitary hormone secretion may be recovered in response to steroid therapy. Improved pituitary MRI after 1–2 weeks of glucocorticoid treatment may provide diagnostic evidence of IgG4-RH.